2006
DOI: 10.1158/1078-0432.ccr-05-1810
|View full text |Cite
|
Sign up to set email alerts
|

Neosquamous Epithelium Does Not Typically Arise from Barrett's Epithelium

Abstract: Purpose: Neosquamous epithelium (NSE) can arise within Barrett's esophagus as a consequence of medical or surgical acid reduction therapy, as well as after endoscopic ablation. Morphologic studies have suggested that NSE can develop from adjacent squamous epithelium, submucosal gland ducts, or multipotent progenitor cell(s) that can give rise to either squamous or Barrett's epithelium, depending on the luminal environment. The cells responsible for Barrett's epithelium self-renewal are frequently mutated durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 33 publications
(22 reference statements)
1
39
0
Order By: Relevance
“…This it does in the short term by covering the wound with an epithelial barrier that is known to lack the malignant potential of its predecessor [11,16,24,25]. However, in the near and long term, this barrier must be durable in its capacity to protect the esophagus against injury, especially from exposure to noxious contents in gastroesophageal refluxates.…”
Section: Neosquamous Epitheliummentioning
confidence: 99%
See 1 more Smart Citation
“…This it does in the short term by covering the wound with an epithelial barrier that is known to lack the malignant potential of its predecessor [11,16,24,25]. However, in the near and long term, this barrier must be durable in its capacity to protect the esophagus against injury, especially from exposure to noxious contents in gastroesophageal refluxates.…”
Section: Neosquamous Epitheliummentioning
confidence: 99%
“…Ablation of BE combined with acid suppression by proton pump inhibitor therapy has been shown to achieve complete reepithelialization of the wounded areas with neosquamous epithelium (NSE) [11,13,14,15,16]. The more recent availability of radiofrequency ablation has led to a resurgence of interest and enthusiasm for the ablative approach because of its reported efficacy, safety, and ease of performance [17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…This new, less invasive therapeutic option is replacing the traditional esophagectomy for treatment of BE with high-grade dysplasia. The neosquamous epithelium that is generated after ablation of BE has been found to be free of oncogenic properties [12]. A recent study demonstrated that total eradication of BE was present in 98% of patients at 2.5 years of follow-up [13].…”
mentioning
confidence: 99%
“…Additional data suggest that both p53 mutation and Ki-67 overexpression are present in columnar epithelium [22] and even in squamous Bars depict median COX-2 immunostain scores in Barrett's HGD/IMC prior to PDT, nondysplastic Barrett's prior to PDT, and neosquamous epithelium following PDT islands following incomplete ablation of BE via argon plasma coagulation or multipolar electrocoagulation [23]. It has also been reported that a focus of neosquamous epithelium had p16 alterations identical to that found in surrounding Barrett's epithelium [24].…”
Section: Discussionmentioning
confidence: 98%